Evaluating Tactical Skills of Amateur Soccer Players With Respect To Their Positions - Mine Taşkın; Turgut Kaplan; Osman Yılmaz; Halil Taşkın (Türk Spor ve Egzersiz Dergisi)
The aim of this study is to evaluate tactical skills of amateur soccer players with respect to their positions. A total of 255 amateur soccer players were examined. These soccer players are playing in different amateur leagues of Turkey. The tactical skill Inventory, which was designed by Elferink-Gemser et al. (7) was used for soccer players. Forwards and Central Defenders had higher tactical skills than did External Defenders, Central Midfielders, and External Midfielders in the positioning and deciding (P lt;0.05). Also, Forwards had higher tactical skills than did External Defenders, Central Midfielders, and External Midfielders in the knowing about ball actions (P lt;0.05). Central Defenders had higher tactical skills than did Goalkeepers, Central Midfielders, External Midfielders, and Forwards in the acting in changing situations (P lt;0.05). The knowing about others soccer players were not statistically significant in the case of all positions (P gt;0.05).In conclusion, it is considered that the tactical skills of the stoppers and forward players are better than the other players. However, it is seen that the tactical understanding of the players has not changed in terms of the knowing about other soccer players.